2013
DOI: 10.3329/bjsir.v48i3.17324
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of effluents of leather industries in Hazaribagh area of Dhaka city

Abstract: This study was conducted at leather industries of Hazaribagh, Dhaka to evaluate the tannery effluent quality. The samples of effluent were taken from seven leather industries and three places around the area of leather industries. The pH, Temperature, Colour, Odour, Electrical Conductivity (EC), Total Dissolved Solid (TDS), Cl-, NO2-, Alkalinity, Dissolved Oxygen (DO), Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD), chromium ion (Cr3+), Suspended Solid (SS), phosphorous, sulphate (SO42-) were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 1 publication
0
8
1
Order By: Relevance
“…Leather industry is one of the key export sectors in Bangladesh. Currently, > 270 registered tanneries are operating in Bangladesh (Rouf et al, 2013;Blacksmith Institute and Green Cross Switzerland, 2013;Hashem et al, 2014). Majority tanneries are situated at Hazaribagh area, located one and a half kilometer northeast to the river Buriganga in Dhaka, as shown in Figure 1 (Shams et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Leather industry is one of the key export sectors in Bangladesh. Currently, > 270 registered tanneries are operating in Bangladesh (Rouf et al, 2013;Blacksmith Institute and Green Cross Switzerland, 2013;Hashem et al, 2014). Majority tanneries are situated at Hazaribagh area, located one and a half kilometer northeast to the river Buriganga in Dhaka, as shown in Figure 1 (Shams et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…They also found that tannery creates the job opportunity. Rouf et al (2013) conducted a study at leather industries of Hazaribagh, Dhaka to evaluate the tannery effluent quality. The samples of effluent were taken from seven leather industries and three places around the area of leather industries.…”
Section: Resultsmentioning
confidence: 99%
“…They also found that tannery creates the job opportunity. Rouf 2013 "Characterization of effluents of leather industries in Hazaribagh area of Dhaka city"…”
Section: Resultsmentioning
confidence: 99%
“…According to scientists, pH of wastewater from leather industry was in the range of 3-9. [21] These revealed that flower-like Cu2O/ZnO was relevant material for practical application in the removal of pigments from leather industry wastewater. In addition, the R 2 values in Table 4 indicated that the pseudo-second-order kinetic was more suitable for describing the adsorption kinetic of TA on Cu2O/ZnO than that of pseudo-first-order model.…”
Section: Effect Of Ph Solution On Adsorption Of Dyementioning
confidence: 99%